Astrovirus gastroenteritis in children - A. M. Komarova; K. D. Ermolenko; M. K. Bekhtereva (LLC "Diagnostics and Vaccines", 2020)
The article provides a detailed analysis of modern publications focused on a studies an astrovirus gastroenteritis. Based on our own examination of 3470 children with acute intestinal infections aged from 1 month to 1 8 years old, who were treated at the Children's Research and Clinical Center for Infectious Diseases, FMBA of Russia, St. Petersburg, from May 201 7 to July 2018 a detailed description of the characteristic epidemiological, clinical and laboratory features of the disease is given. It was shown, that astroviruses remain a significant causative agent of acute intestinal infections in children, accounting for 1.36% of all cases of disease. Among the combined forms of astrovirus infection, associations with rotaviruses, noroviruses and campylobacter spp. are most common. It was established, that the disease is more often observed in boys aged 1 to 3 years. Clinical course of astrovirus infection in children is characterized by an acute or gradual onset with repeated vomiting, moderate intoxication and symptoms of gastroenteritis. Due to the lack of pathognomonic clinical and laboratory features of the course of viral gastroenteritis, diagnosis is necessary using laboratory methods including molecular genetic research methods.